Analysis on the Behavior of Nonpropagating Fatigue Cracks under Steep Stress Gradients - Hao Wu; Qiuying Lu (Advances in Materials Science and Engineering)
A mechanism for the formation of nonpropagating fatigue cracks ahead of a notch root is presented. The stress gradients near the elongated notch root along with the propagation of short crack and the resulting nonpropagating crack lengths anpc are estimated. The local stress which is higher than the unnotched material fatigue limit S0 initiates the crack from a notch root and local steep stress gradient as a very important element leads to the nonpropagating crack. The value of anpc depends on the material properties, and specimen geometry as well as applied loading. The characteristic size of the short crack a0 which depends on the material properties associates with the fatigue stress concentration factor Kf. The estimated values of anpc are in fairly good agreement with the experimental values available.